Perencanaan Jaringan LTE FDD (Frequency Division Duplex) Pada Frekuensi 900 MHZ Di Kota Taluk Kuantan - Arif Fauzar; Linna Oktaviana sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
3GPP sets are the standard for the latest wireless communications technology for Long Term Evolution (LTE). It has been used to meet the needs of consumers today. But only few of development city have implementing it. The rest of the city still not implement it. One of them is the taluk kuantan city. This region has not been deployed by this technology. Due to that reason the design has been made to choose this city. This paper proposes 900 MHz LTE Frequency Division Duplex(FDD)design and simulation through software radio planning atoll. The design process is done by comparing several design scenarios, with reference to research on the previous research paper with the same frequency. The simulation results has obtained in the form of the following parameter i.e. signal level, Carrier to Interference-Noise Ratio (CINR) downlink, CINR uplink and monte carlo analysis. The results were compared to above mentioned parameter that has been published in the previous research result. The number of cells required at least 83 eNodeB. The signal coverage level able to achieve ≤ -85 dBm which better than previous research result (≤-110 dBm), while downlink signal level CINR ≥ 2,479 dB And CINR uplink signal level has ≥ 17 dB. As for the monte carlo simulation able to achieve 81,3%. Finally for throughput uplink and downlink able to achieve ≥ 1 Mbps which is same as previus research result.Keywords: LTE, Atoll, FDD, 900MHz